Mental accounting of product returns - Lee, Chang‐Yuan; Morewedge, Carey K. (Journal of Consumer Psychology, 2023)
AbstractProduct returns incur a substantial financial loss for retailers. We demonstrate how, when, and why cross‐selling during the product returns process can reduce this loss in revenue. We find consumers more readily spend money refunded from product returns than unspent money. We theorize that this refund effect occurs because consumers psychologically realize the loss of money when purchasing products and earmark that money for spending. Thus, consumers feel a smaller psychological loss when spending refunded money than unspent money on a subsequent purchase. In six experiments, we find consumers spend refunded money more freely than unspent money, even more than windfall gains like lottery winnings, on products in similar and different product categories (e.g., groceries vs. apparel). However, the refund effect only holds when consumers do not expect to return products at the point of purchase and before refunded money is commingled with money in other accounts. Our findings identify a new fungibility violation due to mental accounting (i.e., a new source effect), and illustrate its value for generating, validating, and explaining revenue retention strategies.